Attracting and retaining the psychology workforce in public mental health: a study based in Melbourne, Victoria - Madeleine Jaffe; Liza Hopkins; Stephen Halperin (Discover Mental Health)
Abstract Workforce shortages pose a significant barrier to meeting the mental health needs of Australians. This study sought to explore the factors contributing to the recruitment and retention of public (salaried) psychologists and psychologists working as private practitioners within a public mental health service in metropolitan Melbourne. The project involved an online survey of staff and semi-structured interviews. The study found that both private and salaried psychologists identified a number of reasons as to why they were attracted to working in this setting compared with the higher salaries available in full-fee paying private practice. Issues included working with a specific cohort of clients, support of intake and administration teams, flexible working hours, teamwork, the location of the service, the profile of the organisation, and not having to pay room rent or advertise. Salaried staff highlighted the team culture and access to other clinicians for informal discussions as important factors, while private practitioners within the public mental health service most commonly identified financial concerns, including remuneration and failure to attend/cancellations as the biggest challenges. Lack of income was the most commonly cited reason for clinicians’ decisions to leave public mental health. Private practitioners within this setting identified the absence of supervision and professional development, feelings of isolation and lack of team culture as significant deterrents. In sum, numerous issues influence the decisions of psychologists to work in public mental health services rather than, or as well as holding private roles. Public health services need to recognise these and ameliorate identified challenges if they are to attract and retain an adequate psychological workforce.